Do we need a guideline for all: a qualitative study on the experiences of male athletes following anterior cruciate ligament reconstruction - Mehmet Yiğit Gökmen; Fatma Çepikkurt; Mehmet Cenk Belibağlı; Mesut Uluöz; Funda Çoşkun Özyol; Özhan Bavlı; Ergin Karıncaoğlu; Eren Uluöz; Mutlu Türkmen (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Considering the low rate of qualitative studies on athletes with anterior cruciate ligament reconstruction (ACLR), aiming to access in-depth data, we thought that the utilization of the qualitative method would allow us to collect the appropriate and sufficient data to yield novel findings and achieve sound conclusions. The study’s aim was to investigate anterior cruciate ligament (ACL) injury experience processes in athletes who had undergone isolated ACLR, reveal the clinically related milestones, and highlight the necessary gaps. Methods Semi-structured interview techniques, in-depth follow-up questions, and thematic analysis were used to explore the experiences of participants with isolated ACL injuries 1–3 years after surgical treatment. The study was conducted in the Orthopaedics and Traumatology outpatient clinic of the Adana City Training and Research Hospital and included 14 male athletes who had undergone isolated primary ACLR. The study group’s demographic and qualitative data were collected in the first week of September 2023. The member checking process was completed in the third following week. A thematic analysis checklist was used to ensure the reliability of the thematic analysis. The Consolidated Criteria for Reporting of Qualitative Research (COREQ) guidelines were followed. Results The experiences of 14 patients (22.78 ± 3.76 years, all males) were summarized into four themes that emerged from the data analysis process: ‘The Distinctions in the Participants’ Experiences Regarding the Moment of Injury,’ ‘Gathering Information about the ACL Injury,’ ‘Factors That Facilitate The Treatment Process and Reinforce Positive Experiences,’ and ‘Desperate Plight: Main Points of Patients’ Negative Experiences.’ Based on the main themes, there were 14 subthemes. Conclusions Our study revealed that varying perceptions of ACL injury presented by the participants, which were caused by all stakeholders, including themselves, the professional environment, family members, social network, and the healthcare staff, showed that the physical and psychological impacts of the injury were observed in different severity levels at each stage of the process. We believe that an extensive guide for athletes with ACL injuries that includes all components of well-being and displays the required details for the sports club/coach, family/companion, and physician.